THE EFFECTIVENESS OF USING SELF MONITORING APPROACH TO READING AND THINKING (SMART) STRATEGY IN READING COMPREHENSION OF THE SECOND GRADE STUDENTS OF SMP NEGERI 8 LANGSA - Abu Bakar, Muhammad; Rafika (JL3T (Journal of Linguistics, Literature and Language Teaching), 2020)
This research was a quasi experimental research which took place in SMP Negeri 8 Langsa with the total number of population was 117 students and 56 of them were the sample from experimental class and controlled class. This research used pretest and posttest to collect the data. It also used some statistical formulas to analyze the data. It was found that there is a difference in the students’ achievement in reading comprehension between students taught Self Monitoring Approach Reading to Thinking (SMART) strategy and those without using Self Monitoring Approach Reading to Thinking (SMART) strategy. The result of the experimental group is 80.96 and the control group is 65.54 Self Monitoring Approach Reading to Thinking (SMART) strategy has many advantages in teaching reading comprehension. It makes the students more interesting and enjoying the lesson because it is supported by situation. Learning using Self Monitoring Approach Reading to Thinking (SMART) strategy that is accompanied as the background can stimulate, refresh, and support learning.